Inequlity of Economic Development Between Districts in Bali Province - Made Antara (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Economic development is an effort to improve people's welfare, but must be accompanied by growth and distribution of income. The objective of this research are (1) to analyze the level of inequality in economic development between districts/city in Bali Province with and without Badung Regency, (2) di draw the trend lines of economic development between districts/cities in Bali. Source of data is Bali Province Central Statistics Agency. Methof of data analysis uses the Williamson Index. The results of the research showed that (1) The inequality of economic development between districts/city in Bali in 2000-2016 was low but close to moderate, indicated by the Williamson Index average of 0.35. Inequality of economic development between districts/city in Bali for the period 2000-2004 is classified as moderate, indicated by the Williamson Index of 0.38. Badung district has a contribution to increase inequality in economic development between districts/city in Bali as indicated by an increase in the average Williamson Index between districts/city in Bali (without Badung District) of 0.18 (low), while The Williamson index between districts/city in Bali Province (with Badung District) is 0.35 (low to medium).(2) The trendline of inequality in economic development between districts/cities in Bal Province tends to decrease.